Coffee sector: Agritrade Executive Brief Update 2013 - Technical Centre for Agricultural and Rural Cooperation; Eastern Africa Grain Council (Technical Centre for Agricultural and Rural Cooperation, 2013)
Since the 2006/07 season, ACP coffee producers have been playing an increasing role in global coffee production, with strong growth in Eastern Africa. Although the coffee price has declined in recent years (mainly Arabica coffee), in 2012/13 the world coffee price still remained high in historical terms. However, high world prices have not necessarily translated into higher net producer incomes because of increased production costs. This Executive Brief highlights the main international trends in the coffee sector in 2012/13, such as the continued growth in demand for Robusta coffee beans, the rising coffee consumption in emerging countries, and also the rising demand for differentiated coffee (single origin, certified organic or fair trade, as well as coffee pods and instant coffee). The Brief, after analyzing the recent developments in ACP countries, identifies a series of challenges for coffee producers in the ACP, where joint programmes could be envisaged in order to develop new markets and get to grips with evolving value-adding market trends.